63 Improving Safety and Clinical Outcomes for Atrial Fibrillation Ablation: Should Our Threshold for Referral and for Intervention Become Lower?. (3rd June 2016) - Saeed, Yawer; Hussein, Ahmed; Ding, Wern; McClenaghan, Lisa; Meah, Mohamed; Snowdon, Richard; Hall, Mark; Waktare, Johan; Modi, Simon; Todd, Derick; Gupta, Dhiraj
Abstract : Introduction: Historically, the significant risk of complications associated with AF ablation (AFA) has been a potential deterrent for referrers and patients alike. Ours is a high volume EP centre with a fully integrated Electronic Patient Record System that allows for comprehensive data capture and retrieval. We sought to assess success and complication rates of contemporary AFA practice. Methods: We assessed safety and clinical outcome data on follow up for consecutive patients who underwent AFA between Sep 2011 and Aug 2013. A total of 659 AFAs were performed over this period by 6 operators, with 95% done using Carto mapping and a contact force sensing RF catheter. Vascular ultrasound to guide femoral vein access was used in all patients, and general anaesthesia was used in 25%. All patients on prior Warfarin had this continued peri-procedure, with no bridging Heparin used in any case. Clinical follow up data were evaluated for the 425 consecutive patients (69% male, 59.9 ± 10.4 years) who were first time AFAs over this period. Of these, 283 (66.8%) had paroxysmal AF (PAF) and 142 (33.2%) had persistent AF (PeAF), including 33 patients with long standing PeAF. Follow up was available for 405 (94.2%) cases over a mean period of 20 ± 10 months, with a total of 1564 follow up clinic episodes (median 4/patient) reviewed. AF recurrence was deemed to have occurred either if the arrhythmia was documented on ECG, or if the attending clinician treated the patient as for recurrence even without definitive proof, e.g. by starting new antiarrhythmic medication. Results: Major complications occurred in 6/659(0.9%)patients, including 1 pericardial tamponade requiring pericardiocentesis, 1 pulmonary vein stenosis, 2 right phrenic nerve palsies, and 2 cases of groin hematoma requiring blood transfusion. No stroke, TIA, femoral vascular intervention, atrio-oesophageal fistula or death occurred and no case required thoracotomy or extended hospital stay beyond 2 days. Small hematomas, not requiring blood transfusion but delaying hospital discharge by a day, occurred in 9 (1.4%) patients. Clinical freedom from AF for PAF was 55% after single procedure and 86% after a mean 1.3 (1–3) procedures, and for PeAF was 42% after single procedure and 74% after a mean 1.4 (1–3) procedures. 60 (15%) of the patients were on anti-arrhythmic drugs at last follow up, compared to 279/400 (70%) at time of AFA. Conclusions: Complication rates for AFA have decreased markedly in modern practice. Clinical success rates of 85% in PAF and 75% in PeAF can be expected with Contact Force sensing RF catheters, although to achieve these, 30–40% of patients require more than one procedure, and 15% patients need adjuvant AAD.